Hereditarily Irreducible Mappings of Cartesian Product of Continua - Lončar, Ivan (Sarajevo Journal of Mathematics, 2024)
In Section 2 we shall prove that if Cartesian product X× Y of nondegenerate continua admits a hereditarily irreducible mapping f:X× Y→ Z, then w(X× Y)=w(Z). The main section of the paper, Section 3, contains theorems concerning the Whitney maps on continua. In particular, it is proved that the product Π {X_s:sS} of nondegenerate continua admits a Whitney map for C(Π {X_s:sS}) if and only if it is metrizable. 2000 Mathematics Subject Classification. Primary 54B20, 54F15